International studies in the Philippines mapping new frontiers in theory and practice - Adiong, Nassef Manabilang; Cruz, Frances Antoinette (New York Routledge, 2020)
"How can local experiences and the social transformation generated by modernity help to enrich our understanding of the international? What might a version of the much-discussed "non-Western International Relations (IR)" look like? What continuities and discontinuities from the Philippine experience in particular can be useful for understanding other post-colonial polities? The Philippines makes a fascinating case study of a medium-sized, developing, post-colonial, multi-ethnic and multi-cultural state in Southeast Asia. Cruz, Adiong and their contributors map horizons of non-Western approaches in Philippine experiences of IR, rooted in the Global South, and in local customs and practice. Examining both theory and praxis, they explore issues as diverse as pre-colonial history, diplomacy, religion, agrarian reform and the Philippines' relationship with key regions in the Global South. The book will appeal to researchers interested in Southeast Asian Studies and alternative perspectives on IR"--
Butuan in the Pre-colonial Southeast Asian International System: Reconstructing International History from Text, Memory, and Artifacts -- José Rizal Attacks Imperialism Softly: Comprehending the Depths of Psychological Conversion and the Temptations of Violent Solutions -- Constantino Revisited: The 'Miseducation' and Diplomacy of the Filipinos -- Publishing on the 'International' in the Philippines: A Lexicometric Inquiry -- Internationalizing Pagdamay and Palakasan: A Philippine Perspective on Duterte Foreign Policy -- Discursive Experiments in Vernacularizing International Studies in the Philippines -- The Case of Agrarian Reforms in Philippine-USA Relations: A Biopolitical Perspective -- Marginalization of Interests: The Case of Philippine-Middle East Relations -- Political and Economic Perspectives on Diversification in Philippine-South America Relations -- Religious Actors in the International Sphere: The Case of the National Council of Churches in the Philippines -- Religious Expertise, Public Theology and Philippine Regime Compliance -- Securitization of the Global War on Terror and Counterterrorism Cooperation against the Abu Sayyaf Group -- Sexploitative Human Trafficking In, Out and Beyond the Philippines: A Liquid Problem in a Cosmopolar International System -- Conclusion: Small Statism and the Non-issue of IR in the Philippines.
Includes bibliographical references and index.
Keywords: International relations; Postcolonialism -- Philippines; Philippines -- Foreign relations; Philippines -- Social policy